INFORMATION TECHNOLOGY FOR THE STUDY OF CELL ADAPTATION TO HYPOXIA: THE FOCUS IS ON MITOCHONDRIA - Liabakh, К. G. (Medical Informatics and Engineering, 2020)
Background. It is offered a concise description of the information technology to study the adaptation of cells to hypoxia by special redistribution of mitochondrial oxidative power by different ways. Our goal was to represent a concise description of this technology based on a mathematical model and propose an example of its application for calculating the parameters of cell oxygen mode under different ways of mitochondrial distribution. Materials and methods. Results. Comparison of the oxygen regimes of the cell with a uniform and uneven distribution of mitochondria showed that during hypoxia, an increase in the oxidative power of evenly distributed mitochondria can increase the rate of oxygen consumption, while hypoxia in the cell increases. Under uneven of mitochondria distribution oxygen mode improved, hypoxia weakened. The movement of mitochondria towards the capillary is able to facilitate cellular adaptation. It was possible to reduce hypoxia and maintain the oxygen consumption rate at the constant level. Conclusions. An information technology has been developed to calculate the parameters of the oxygen regime of the cell at various distributions of mitochondria in it. When О2 diffusion transport worsens, mitochondrial spatial rearrangement expands the cell's ability to compensate for the worsening diffusion conditions.